Internet of Things based solar panel cooling and monitoring system - Febiola, Anjelika; Dewi, Citra; Mirshad, Emilham; Mulya, Rudi (Journal of Industrial Automation and Electrical Engineering, 2025)
Solar energy is one of the renewable energy sources that has great potential in Indonesia, due to its abundant availability and zero greenhouse gas emissions. However, the performance of solar panels can degrade due to high temperatures generated by continuous exposure to sunlight. This research aims to design and implement an effective cooling system to increase the output power of solar panels. The system is designed with a real time remote monitoring feature using the Blynk application, and is equipped with an automatic data logging  system  into  Google  Sheets.  The  cooling  mechanism  is carried out by spraying water onto the surface of the solar panel which is activated based on a predetermined temperature threshold value (set point). The test results show that the system is able to reduce  the  panel  temperature  by  5.46°C  and  increase  the  output power  by  1.76  W.  The  ratio  of  power  increase  to  temperature decrease is recorded at 3.1 W/°C, which proves that the system is effective   in   keeping   the   panel   temperature   below   40°C   and contributes significantly to the improvement of solar panel performance